Chinese Ethnic Communication Pattern in the Environment of Indigenous People in Lhokseumawe, Indonesia - Muhammad Saleh; Syukur Kholil; Ahmad Tamrin Sikumbang (Budapest International Research and Critics University, 2018)
This paper entitled Chinese Ethnic Communication Pattern in the Environment of Indigenous People in Lhokseumawe, Indonesia. To be used as the basis for the formulation of the research problems written in this paper, namely: how is the communication pattern of LhokseumaweChinese ethnic in the indigenous people in Lhokseumawe. So that the writer can find the communication pattern of LhokseumaweChinese ethnic in the indindigenous people in Lhokseumawe, as the writing patron the writer uses the method in this study is a qualitative research method with the aim to explain the phenomenon deeply, through a phenomenological approach. The process of data collection techniques through observation, unstructured interviews, and documentation while data analysis techniques are carried out in three ways, data reduction, displaying data, and drawing conclusions. To strengthen this research is supported by three theories, namely the theory of Symbolic Interaction, Turgic Drama theory, and Goffman'sSelf Presentation. The results of this study indicate that, the communication pattern of LhokseumaweChinese ethnic in the indigenous people in Lhokseumawe is done by cultural adaptation. Chinese ethnic communities try to find sympathy for indigenous people by promoting symbolic interaction and identity manipulation.